Integrated Group of Companies as Subject of Public Policy by the Case of JSC «Gazprom-Media Holding» - A. E. Kostin (Управленческое консультирование)
The author focuses on the consideration of the concept of integrated groups of companies by J. Pappe as an analytical tool for studying subjects of corporate interests and mechanisms of corporate representation in the political space of modern Russia. In the article attempts to substantiate the author’s position on the applicability of the concept of integrated business groups not only within the framework of economic science, but also to reveal its significance for political science using the case-study method of JSC Gazprom-Media Holding, which is one of the Russian integrated businesses -groups and at the same time a large corporate group of interests.